MODEL PENYELESAIAN TINDAKAN PELANGGARAN PEMANFAATAN BIOTA LAUT MENURUT HUKUM ADAT MELAYU MANDAH RIAU - Tri Mukti; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Violation of the use of marine biota in Mandah Subdistrict occurs because in Mandah Subdistrict the population is mostly fishermen. From this abundance of sea and river products, there are some irresponsible people who catch fish by means of centrums and poisoning. Which will result in the exhaustion of large fish populations down to small fish and this is very damaging to the surrounding environment. As happened in the Simar village, Mandah District, because of his fishing activity at the center, he himself was hit by the throttle. This is a concern for the Mandah Malay Customary Institution to determine the laws that apply to its society. This research is classified as sociological research, because in this study the author directly conducted research at the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Riau Malay Customary Institution, Mandah District, while the population and sample were all parties related to the problems studied in this study, the data sources used, primary data, and secondary data, and tertiary data, data collection techniques in this study. conducted by interview, and literature study. The results of the research include: First, the model for solving crimes using marine biota according to LAMR Mandah, the community is not allowed to buy the proceeds from their arrest and will be followed up by the authorities if it is still sustainable. Second, the role of LAMR in its duties is to guide, develop, and implement as well as guard the customary values of Malay Culture to the community. Third, one of the obstacles faced is the lack of awareness of the perpetrators to stop fishing using a centrum tool, the lack of awareness that if this continues it will have an impact on the population of extinct biota, and usually the modus operandi that often occurs by the perpetrators doing their actions at night. , so that it seems secretive and when community activities are gone. Keywords: Utilization of Marine Biota, Riau Malay Traditional Institution, Actors